Paralytic shellfish toxin content is related to genomic sxtA4 copy number in Alexandrium minutum strains - Stüken, Anke; Riobó, Pilar; Franco, José; Jakobsen, Kjetill S.; Guillou, Laure; Figueroa, Rosa I. (Frontiers in Microbiology, 2015)
Dinoflagellates are microscopic aquatic eukaryotes with huge genomes and an unusual cell regulation. For example, most genes are present in numerous copies and all copies seem to be obligatorily transcribed. The consequence of the gene copy number for final protein synthesis is however not clear. One such gene is sxtA, the starting gene of paralytic shellfish toxin (PST) synthesis. PSTs are small neurotoxic compounds that can accumulate in the food chain and cause serious poisoning incidences when ingested. They are produced by dinoflagellates of the genera Alexandrium, Gymnodium and Pyrodinium. Here we investigated if the genomic copy number of sxtA4 is related to PST content in Alexandrium minutum cells. SxtA4 is the 4th domain of the sxtA gene and its presence is essential for PST synthesis in dinoflagellates. We used PST and genome size measurements as well as quantitative PCR to analyze sxtA4 copy number and toxin content in 15 A. minutum strains. Our results show a strong positive correlation between the sxtA4 copy number and the total amount of PST produced in actively growing A. minutum cells. This correlation was independent of the toxin profile produced, as long as the strain contained the genomic domains sxtA1 and sxtA4.